Pengelolaan Kelas Terhadap Siswa Tuna Rungu-Wicara Di Kelompok A1 PGRA Mamba’ul Hisan - Aprilia Rahmawati; Juhaeni Juhaeni; Ayu Kinasih; Nur Shibyany; Siti Aisah (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
Children with special needs including children who are deaf-speech are children who have the right to get teaching and develop according to their potential. Like normal children in general, children who are deaf-mute have problems that must be resolved so that they can perform maximally. One of them is by providing education. Education is very important in life to eradicate ignorance. Teachers and parents must also be seen in the teaching process of students. For this reason, class management must also be in accordance with the conditions of students so that students are interested and can follow the learning well and in accordance with what is expected